Skills Implications of Botswana's Diamond Beneficiation Strategy - World Bank (Washington, DC, 2015)
This note examines the skills implications of the beneficiation strategy, particularly those of diamond cutting and polishing. In addition to reviewing the government s plans to develop downstream activities and their implementation, the note offers employment projections based on the potential success of diamond beneficiation efforts. For this purpose, an input-output simulation is used to show how output linkages arising from the production of polished diamond exports will impact labor in various sectors of the economy. The analysis is based on primary data and information collected through interviews with relevant stakeholders in the diamond industry, as well as secondary data from official sources. The note suggests that in the last five years, Botswana has made considerable progress in establishing a local cutting and polishing industry, but that the success of this industry depends on the creation of concomitant skills. By 2010, the industry had already created close to 3,000 direct jobs in 16 cutting and polishing factories, in line with governmental targets. The input-output simulation shows, that the output linkages arising from the input demands associated with processing rough diamonds, valued at $550 million by the 16 aforementioned factories has the potential to create over 6,000 indirect jobs in the country. The cutting and polishing industry is still in the development phase and needs a dynamic policy environment in order to remain relevant at all stages of its development. Policies are needed in particular to: create industry-specific skills (with clear skills transfer targets, or deadlines), establish technology links between the diamond hub and the innovation sector, facilitate rough diamond trading, and expand the capacity of the Botswana Training Authority (BOTA) to accredit cutting and polishing programs within industry factories.